Technical Efficiency of Wheat Production in the Gezira Scheme (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was carried out to measure the technical efficiencyof wheat production in the Gezira scheme and to determine the mostimportant socio-economic factors affecting this efficiency, using thestochastic production frontier model. Primary and secondary data wereused. The former were collected from a random sample of 100 farmersfrom Waddel Mansi sector of the Gezira scheme, while the latter werecollected from relevant sources. The results showed that the meantechnical efficiency was 0.73, which means that the scheme produced73% of the possible wheat production at the current levels of productioninputs and technology. In other words, wheat production could have beenincreased by 27%, at the same levels of inputs had farmers beentechnically efficient. The results also showed that 97% of wheat outputdeviations from normal were caused by differences in farmers' levels oftechnical efficiencies and were not due to the out of control randomnature of the agricultural production. Wheat area, sowing date, degree ofinfection with pests and diseases, number of insufficient irrigations andfarmers' experience appeared to be the most important factors determiningwheat output in the Gezira scheme. The off-farm income appeared to havenegative effects on wheat production, because of its timing contradictionswith some important agricultural operations. The farmers' gender, landtenure, land preparation, marital status and farm location with respect tothe irrigation canal, represented the most important socio-economicfactors determining farmers' efficiencies of wheat production in theGezira scheme.
Keywords: Fadel Mola; frontier; technical; efficiency; allocative; conventional; random